Agarophyton transtasmanicum sp. nov. from Australia and New Zealand. Issue 3 (3rd May 2020) - Preuss, Maren; Muangmai, Narongrit; Nelson, Wendy A.; Guillemin, Marie-Laure; West, John A.; Zuccarello, Giuseppe C.
ABSTRACT: The Gracilariaceae is a species-rich family, with a number of members having high commercial value as sources of agar. Members of this family are also known for their phenotypic plasticity and convergent morphologies, resulting in considerable taxonomic confusion. Over the past two decades, two species of Agarophyton (previously part of Gracilaria ) have been recognised in New Zealand with very similar morphologies and growth habits, and they have been incorrectly grouped as Agarophyton chilense. Agarophyton chilense is distributed in Chile and New Zealand and is genetically distinct from Agarophyton sp. from Australia and New Zealand. We name this new species A. transtasmanicum sp. nov . Morphologically A. transtasmanicum has fewer medullary cell layers and a more abrupt transition in cell size between cortex and medulla than A. chilense . The cox 1 and rbc L dataset grouped A. transtasmanicum as sister to A. tenuistipitatum with high support. Clarifying the distinctions between A. chilense and A. transtasmanicum will enable further research, including investigating differences in distribution patterns, physiology, ecology, and chemical composition of these two Agarophyton species.